The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3390/nu6010231
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean Diet and Nutritional Adequacy: A Review

Abstract: The Mediterranean dietary pattern, through a healthy profile of fat intake, low proportion of carbohydrate, low glycemic index, high content of dietary fiber, antioxidant compounds, and anti-inflammatory effects, reduces the risk of certain pathologies, such as cancer or Cardiovascular Disease (CVD). Nutritional adequacy is the comparison between the nutrient requirement and the intake of a certain individual or population. In population groups, the prevalence of nutrient inadequacy can be assessed by the prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
216
0
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(235 citation statements)
references
References 66 publications
7
216
0
12
Order By: Relevance
“…Aparte de una mejor calidad de la grasa y de sus efectos antiinflamatorios y antioxidantes, también se ha demostrado que estar en los niveles más altos de adherencia a un patrón dietético mediterráneo se asocia con un menor riesgo de ingesta inadecuada (138). Las principales características de la dieta mediterránea son el uso habitual del aceite de oliva y la abundancia de alimentos derivados de plantas, que incluyen frutas, verduras, legumbres, nueces y granos enteros, asegurando así un amplio suministro de fibra y antioxidantes, todos ellos agentes protectores del telómero (132).…”
Section: Patrones Dietéticosunclassified
“…Aparte de una mejor calidad de la grasa y de sus efectos antiinflamatorios y antioxidantes, también se ha demostrado que estar en los niveles más altos de adherencia a un patrón dietético mediterráneo se asocia con un menor riesgo de ingesta inadecuada (138). Las principales características de la dieta mediterránea son el uso habitual del aceite de oliva y la abundancia de alimentos derivados de plantas, que incluyen frutas, verduras, legumbres, nueces y granos enteros, asegurando así un amplio suministro de fibra y antioxidantes, todos ellos agentes protectores del telómero (132).…”
Section: Patrones Dietéticosunclassified
“…In support of all these diet-health connections, recent studies have clearly underlined the nutritional quality of an MDP. Persons who adhere closely to an MDP fulfil their micronutrient requirements much better than persons on a typical Western diet (61,62) . Computer-assisted modelling of individual diets identified that the most important foods that enable people to fulfil nutritional requirements (except for vitamin D) are those characteristic of the MDP (63) .…”
Section: Development Of the Med Diet 40 Frameworkmentioning
confidence: 99%
“…A plethora of previous research highlighted the Mediterranean diet as an ideal paradigm of a health promoting diet (1,2) that can play an important role in the prevention of cardiometabolic diseases (3,4). Since the pioneering work of Keys et al (5), in Crete, Greece, the cradle of the Mediterranean diet, several studies showed that the benefits of the Mediterranean diet are primarily due to the high intake of vegetables, fruits, cereals (preferably whole grain),the moderate intake of fish, dairy products and red wine, and to the limited intake of meat (6, 7).…”
Section: Introductionmentioning
confidence: 99%